Following changes in balance and cognitive performance on healthy middleaged people: Evaluation of the effect of two types of concurrent training - Umut Canli; Pablo Prieto-González (Termedia Publishing House, 2023)
Purpose The study aimed to compare the effects of two different concurrent training protocols applied to healthy middleaged individuals on balance parameters and cognitive functions. Methods Thirty-three middle-aged adults voluntarily participated in this study. A randomised, between-group design (Strength+Aerobic Group [SAG] and control group Aerobic+Strength Group [ASG]) was used. After collecting data related to the main characteristics of the subjects (i.e., age, sex, medical history, smoking habits), the following assessments were made: Subjects' physical activity level, balance parameters, and inhibition and attention indicators. The intervention lasted 13 weeks (2 sessions per week, 50 minutes per session). Results Both protocols (SAG and ASG) significantly improved balance performance. However, as for the group-by-time interaction, no significant difference between the two groups were observed in any of the parameters assessed (F(1-31) = 0.843; 0.760; 0.612; 0.656; p > 0.05). Thus, it was found that participating in either the SAG or ASG groups had no significant influence on attention accuracy, reaction time, total number of matters processed (participants' psychomotor speed), and non-marked letters (selective attention) (post-test-pre-test difference: F(1-31) = 0.239, 0.337, 0.738, 0.414; p > 0.05). It was also observed that both training programs resulted in similar improvements in all balance characteristics and cognitive parameters. Conclusions It was found that the order of strength or aerobic exercises in the concurrent training for improving balance and cognitive parameters in healthy middle-aged individuals is not significant.